Methanol leaf extract of Actinodaphne sesquipedalis (Lauraceae) enhances gastric defense against ethanol-induced ulcer in rats - Hanita Omar; Noraziah Nordin; Pouya Hassandarvish; Maryam Hajrezaie; Ainnul Hamidah Syahadah Azizan; Mehran Fadaeinasab; Nazia Abdul Majid; Mahmood Ameen Abdulla; Najihah Mohd Hashim; Hapipah Mohd Ali (Dove Medical Press Ltd., 2024)
Non-Indexed Publication